TOURISM AS A TOOL FOR ECONOMIC DEVELOPMENT: IDENTIFICATION OF DETERMINING FACTORS - Cárdenas-García, Pablo Juan (PEOPLE: International Journal of Social Sciences, 2024)
Currently, a significant number of countries are betting on tourism as an economic activity on which to base their economic development, given that most international organizations recognize that tourism can become a tool for economic development, especially in less developed countries. However, on the part of the scientific literature there is no defined current on the capacity of tourism to become an instrument with which to improve the living conditions of the population residing in receiving countries. In this sense, in the scientific literature there are numerous investigations that have dealt with analysing the relationship between tourism and economic growth, a large part of these works coinciding that there is a causal relationship between both variables, but the same does not happen when the relationship between tourism and economic development. Among works that have analysed this relationship, there is no uniform current on the relationships that exist between tourism and economic development, being different the variables that have been used in these works to measure tourism and economic development, and being applied in different areas of analysis. Indeed, since the appearance of the first works that have analysed the relationship between tourism and economic development, approximately ten years ago, a large number of investigations have emerged on this relationship, for which it is interesting to carry out an evaluation of the main models econometrics that have been used, as well as the main empirical findings that have been reached in this work. In this context, this work highlights a comprehensive review of a large number of peer-reviewed articles that analyse the relationship between tourism and economic development, providing a general description of the theoretical framework that supports the relationship between these two variables, as well as the main results that have been obtained in these works, which will allow establishing the position of the scientific literature regarding the capacity of tourism as an instrument of economic development. This work, therefore, contributes to the scientific literature by answering the question: what is the relationship between tourism and economic development?